Cover Picture: Accelerated Discovery in Photocatalysis using a Mechanism‐Based Screening Method (Angew. Chem. Int. Ed. 13/2016). Issue 13 (18th March 2016) - Hopkinson, Matthew N.; Gómez‐Suárez, Adrián; Teders, Michael; Sahoo, Basudev; Glorius, Frank
Abstract : Screening methodologies can greatly accelerate the discovery of new chemical reactions. In their Communication onpage 4361 ff., F. Glorius et al. describe a conceptually novel mechanism‐based screening approach using luminescence spectroscopy to directly investigate the key quenching step in photocatalysis. As illustrated in the cover image, various photocatalysts and potential substrates undergo "speed dating" with the observation of quenching signifying a promising combination that can be applied in new light‐promoted reactions.